Synthesis of Unsymmetrical Methylenebisphenol Derivatives - Guieu, Samuel (2013)
A simple and efficient route towards unsymmetrical methylenebisphenol derivatives is reported. This straightforward strategy avoids the use of harmful or dangerous chemicals, allowing the synthesis of highly functionalized bisphenyls with no need of protecting groups. The alkylation of the phenyl ring is selective for the para position of the hydroxyl substituent. All methylenebisphenols were obtained in a completely regioselective manner and isolated in high yields.